Why It's Not Time for Health Care Rationing. Issue 2 (4th March 2015) - Ubel, Peter A.
Abstract: In the last few years, the U.S. health care system has seemingly been gripped by "back to the nineties" fever. But there is a notable change in professional debates about how to better control health care costs. Discussion of health care rationing, which was hotly debated in the nineties, has become much more muted. Is health care rationing passé? I contend that debates about health care rationing have waned not because the need to ration has dwindled nor because ethical debates about how or whether to ration have been resolved. They have declined because the word "rationing, " and unrelated concepts such as cost‐effectiveness analysis, have been replaced by terms—"parsimony, " "value, " and "CER"—that are not burdened by emotional and historical baggage. Sometimes the best way to promote healthy moral debate is to turn to new words that don't carry the burden of past debates.